Hypofractionated High-Dose Irradiation with Positron Emission Tomography Data for the Treatment of Glioblastoma Multiforme. (22nd May 2014) - Miwa, Kazuhiro; Matsuo, Masayuki; Ogawa, Shin-ichi; Shinoda, Jun; Asano, Yoshitaka; Ito, Takeshi; Yokoyama, Kazutoshi; Yamada, Jitsuhiro; Yano, Hirohito; Iwama, Toru
Abstract : This research paper presents clinical outcomes of hypofractionated high-dose irradiation by intensity-modulated radiation therapy (Hypo-IMRT) with 11 C-methionine positron emission tomography (MET-PET) data for the treatment of glioblastoma multiforme (GBM). A total of 45 patients with GBM were treated with Hypo-IMRT after surgery. Gross tumor volume (GTV) was defined as the area of enhanced lesion on MRI, including MET-PET avid region; clinical target volume (CTV) was the area with 5 mm margin surrounding the GTV; planning target volume (PTV) was the area with 15 mm margin surrounding the CTV, including MET-PET moderate region. Hypo-IMRT was performed in 8 fractions; planning the dose for GTV was escalated to 68 Gy and that for CTV was escalated to 56 Gy, while keeping the dose delivered to the PTV at 40 Gy. Concomitant and adjuvant TMZ chemotherapy was administered. At a median follow-up of 18.7 months, median overall survival (OS) was 20.0 months, and median progression-free survival was 13.0 months. The 1- and 2-year OS rates were 71.2% and 26.3%, respectively. Adjuvant TMZ chemotherapy was significantly predictive of OS on multivariate analysis. Late toxicity included 7 cases of Grade 3-4 radiation necrosis. Hypo-IMRT with MET-PET data appeared to result in favorable survival outcomes for patients with GBM.